Efficacy of Static and Dynamic Exercise Interventional Protocol in Patients with Non-Specific Neck Pain - Danishta; Kumar, Mayank; Gupta, Bandita; Upadhyay, Ishika; Rajbhar, Ruma (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
Aim: To see the efficacy of dynamic and static neck exercise interventional protocol in patients with nonspecific neck pain. Objectives: To evaluate the efficacy of static and dynamic exercises in patients with nonspecific neck pain and compare the efficacy of dynamic and static neck exercise interventional protocol when given alone or in combination. Methods: 30 Subjects were selected for the study. Sampling was done by random selection method and then groups of 10 subjects were assigned to each group by chit-chat method. Each subject was given an Ultrasound for 5 min before exercises in each group. It was a 5-week (6 days a week) intervention study. Conclusion: Dynamic and static exercise protocols effectively improve the range of motion and functional activities in nonspecific neck pain patients. However, a significant difference has not been found when these exercises are combined or alone.